Right Ventricular Exclusion and Univentricular Palliation for Failed One and a Half Ventricle Repair for Ebstein's Anomaly - Sasikumar, Navaneetha; Krishna Manohar, Soman R.; Philip, Saji; Cherian, Kottoorathu Mammen; Suresh Kumar, Raghavannair (Heart, lung & circulation, 2013)
A 20 year-old male was diagnosed to have Ebstein's anomaly with severe right ventricular dysfunction. He was taken up for 1.5 ventricle repair. Post procedure, there was difficulty in weaning from cardiopulmonary bypass due to progressive right ventricular dilatation compromising the systemic output. An atrial septectomy did not help. Progressive right ventricular dilatation compressing the left ventricle, demonstrated on transoesophageal echocardiogram, prompted us to perform a right ventricular exclusion and univentricular palliation. The patient was successfully weaned off cardiopulmonary bypass and had a smooth postoperative recovery. Judicious use of right ventricular exclusion and univentricular palliation could be an effective bailout strategy in difficult surgical scenarios in Ebstein's anomaly.